PENGARUH STRATEGI PEMBELAJARAN KONTEKSTUAL DAN KONSEP DIRI TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Hellinawati, Hellinawati; Muhammad, Damris; Kamid, Kamid (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
The purpose of this study is to prove the existence of the learning effect of Contextual Teaching and Learning (CTL) strategy and the Self-Concept Toward Understanding Math Concepts Grade VIII MTs of Bangko. This research is the quantitative research, that’s the quasi-experimental. Data collection instruments such as questionnaires and tests the concept of self-understanding mathematical concepts. The research result are: (1) There is the influence of contextual teaching and learning strategies for understanding mathematical concepts. (2) There is the influence of self-concept to the understanding of mathematical concepts. (3) There were no effects of contextual teaching and learning strategies for understanding mathematical concepts to students who have a high self- concept. (4) There were no effects of contextual teaching and learning strategies for understanding mathematical concepts to students who have a low self-concept. (5) There is no interaction between learning strategy and self-concept. In this study it was found that CTL and self-concept in learning influence students' understanding of mathematical concepts, but CTL has a powerful role in increasing the understanding of mathematical concepts, regardless of whether the student is a high or low self-concept. Keyword: Contextual Teaching and Learning (CTL) Strategy, Self-Concept, and Understanding of Mathematical Concepts.